The Relationship between Multiple Intelligences and the Age of Institutional Teachers - Jouzdani, Mani (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This study tends to investigate whether the age of English as a Foreign Language (EFL) institutional teachers in Isfahan/Iran have any relationship with the intelligence they prefer to use, whether consciously or unconsciously, in teaching English as a foreign language. The intelligences considered for the purpose of this study are namely Interpersonal and bodily/kinesthetic intelligences proposed by Gardner (1983). In order to conduct this investigation a standardized questionnaire based on Berman (2001) and Christison and Kennedy (1999) Multiple Intelligence (MI) checklist was given to 117 male institutional teachers and the results were calculated using a paired T-test also ten interviews were conducted at the end of the case study on ten teachers after observing their classes. The results suggested that as the age of the teacher increase, to some extent, their preference in using interpersonal intelligence over bodily/kinesthetic intelligence increases as well. Also the case study conducted on one of the institutional teachers proved that teachers of older ages prefer using interpersonal intelligence over bodily/kinesthetic one.